Benign or Malignant Anomaly? Very High Takeoff of the Left Main Coronary Artery above the Left Coronary Sinus - Rosenthal, Robert L. (Texas Heart Institute, 2012)
Very high takeoff of the left main coronary artery in the absence of another coronary anomaly is a rare finding. The pathologic consequences of this anomaly are unclear, and the literature on this subject does not agree on whether the condition is dangerous. We present our findings in 2 patients who were discovered to have this anomaly upon noninvasive computed tomographic coronary angiography, and we discuss our analysis of the literature and our management of these patients.